Perioperative transfusion in pancreatoduodenectomy: The double-edged sword of pancreatic surgeons. Issue 49 (December 2017) - Park, Hyeong Min; Park, Sang-Jae; Shim, Jae Ryong; Lee, Eung Chang; Lee, Seung Duk; Han, Sung-Sik; Kim, Seoung Hoon
Abstract : Abstract: We designed the study to clarify the prognostic significance of perioperative (preoperative, intraoperative, and postoperative) red blood cell (RBC) transfusion following pancreaticoduodenectomy (PD) for periampullary cancers. This study retrospectively analyzed 244 periampullary cancer patients (pancreatic cancer, 124 patients; bile duct cancer, 63 patients; and ampullary cancer, 57 patients) treated by PD from June 2001 to June 2010 at the National Cancer Center, Korea (NCC2017-0106). A total of 112 (46%) of 244 patients had received transfusion (preoperative, 5%; intraoperative, 17%; and postoperative, 37%). The 5-year survival rate of patients without perioperative transfusion was 36%, whereas that of patients with a transfusion was 25% ( P  = .04). Perioperative transfusion and intraoperative transfusion were found to be independent poor prognostic factors [relative risk (RR): 1.52 and 1.95, respectively]. The independent factors associated with perioperative transfusion were being female, operation time >420 minutes, portal vein (PV) resection, and preoperative serum hemoglobin (Hb) < 12 mg/dL. As the amount of perioperative transfusion increased, overall survival (OS) decreased. Perioperative transfusion, especially intraoperative transfusion was an independent prognostic factor for survival after PD. Therefore, for patients with periampullary cancer, intraoperative bleeding and operation time should be minimized and preoperative anemia corrected. Abstract : Supplemental Digital Content is available in the text